Fixation of posterior malleolus fractures through posterior access in the ankle: case series - Masuda, Vitor Yoshiura; Pereira, Vinicius Felipe; Baumfeld, Daniel Soares; Cruel Neves, Caroline Marques dos Santos Cavaleiro; Nery, Caio; Mansur, Nacime Salomão Barbachan (Scientific Journal of the Foot & Ankle, 2018)
Objective: The aim of this study is to present the preliminary results of posterior malleolus fixation in a case series by evaluating clinical and radiographic outcomes as well as possible complications related to this approach. Methods: This study involved a case series of 7 patients with posterior malleolus fractures, either isolated or associated with other tibiotarsal injuries, who were surgically treated and evaluated from January 2014 to December 2016 in one of the hospitals of our service. The patients were evaluated for consolidation, pain (Visual Analog Scale (VAS) score), function (American Foot and Ankle Society (AOFAS) score), surgical wound complications and joint degeneration in the postoperative period. Results: The mean follow-up was 66 weeks. All patients presented clinical and radiographic consolidation of the fractures by the sixth week of the follow-up. The mean pain score according to the VAS was 1.5 and the mean AOFAS score was 92.5. At the end of follow-up, no clinical or radiographic evidence of joint degeneration was observed. Conclusion: Posterior access is a viable alternative that provides good results with few complications for the treatment of posterior malleolus fractures. Level of Evidence IV; Therapeutic Studies; Case Series.